PENJATUHAN PUTUSAN BEBAS PADA PELAKU TINDAK PIDANA KEKERASAN FISIK DALAM RUMAH TANGGA TERHADAP ISTRI (Studi Kasus Pada Putusan Pengadilan Negeri Pekanbaru Nomor: 451/Pid.Sus/2017/Pn.Pbr) - SUSILO, MITA ISTU (Dinamika Hukum, 2019)
The purpose of this research is to examine the criminal application of the perpetrators of domestic violence against the wife of the Pekanbaru state Court Decree number: 451/Pid. Sus/2017/PN.Pbr. Reviewing the judgment of judges in dropping Free decision on perpetrators of domestic violence against the wife on the ruling of Pekanbaru District Court number: 451/Pid. Sus/2017/PN.Pbr. The method of approach in writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses the Skunder data. Data collection techniques using library studies. To analyze the data, researchers use qualitative descriptive analysis methods. Criminal application to the perpetrators of domestic violence against wives in Pekanbaru District Court Decree number: 451/Pid. Sus/2017/PN. PBR, the defendant ALENDRI Als ALEN Bin SARUJI is not legally proven and convincing guilty Commit a criminal offence in the household, as regulated and threatened by criminal in the alleged offence of article 44 paragraph (1) of LAW No. 23 year 2004 on the elimination of violence in the household and the second indictment of article 44 paragraph (4) of LAW No. 23 Th. 2004 ON The elimination of domestic violence, so that the Terdaka must be freed from both claims and restore the defendant's rights in their abilities, positions, and dignity. Consideration of judges in the breach of criminal acts of domestic violence against wives on the ruling of Pekanbaru District Court number: 451/Pid. Sus/2017/PN. PBR based on evidence of witness, proof of goods, letter of Visum et The investigation and the elements in the provisions of article 44 paragraph (4) of law No. 23 of 2004 on the elimination of violence in households. Based on the results of the test the evidence suggests that the results of the Visum et investigation explain that on the examination is not found signs of violence, in addition to the information submitted by the witnesses in the trial no one sees In a direct quarrel between the defendant and the witnesses, the witnesses only knew the incident from the victim's testimony. Keywords: Criminal acts of physical violence in the household, the judgment of judges.